Molecular differences between GM- and non-GM crops over-estimated? - Ammann, Klaus (Nepal Journal of Biotechnology, 2010)
Peer reviewed contribution available on the following websites: Public Research Initiative: www.pubresreg.org European Federation of Biotechnology: http://www.efb-central.org/ Nepal Journal of Biotechnology. Jan. 2011, Vol. 1, No. 1 : 31-48